2010
DOI: 10.1089/fpd.2010.0533
|View full text |Cite
|
Sign up to set email alerts
|

Foodborne Nematodal Infections in Hospitalized Patients from a Southwestern Romanian County

Abstract: Although trichinellosis cases decreased in this county, public health authorities must remain aware because new outbreaks may occur at any time as it happened in the neighboring counties. Regarding geohelminthiasis, parents must be aware of the potential risk of acquiring these infections and the major complications that may follow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…As in other Romanian clinical surveillance studies [10,16,17,20], the moderately severe course of disease was detected most frequently, and the hospitalization period ranged between 8 and 14 days for most of the patients. The mean eosinophil count and ESR were significantly higher in adults than in children, as in the prior extensive comparative surveillance [15].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…As in other Romanian clinical surveillance studies [10,16,17,20], the moderately severe course of disease was detected most frequently, and the hospitalization period ranged between 8 and 14 days for most of the patients. The mean eosinophil count and ESR were significantly higher in adults than in children, as in the prior extensive comparative surveillance [15].…”
Section: Discussionsupporting
confidence: 70%
“…As well as adults being involved in the slaughtering process and in preparing the traditional pork products, their predominance may also be explained by the demographic characteristics of the population in this area. Dependence on home-made traditional products is likely to prevail in persons on low incomes, and most of the patients in this study were unemployed, as in other studies performed in the neighbouring counties: Caras-Severin (31%) [16] and Hunedoara (40.1%) [17]. The general rate of 2.9% unemployed people in this region could explain the high percentage of trichinellosis patients from this social category.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Data from 269 hospitalised patients between 1996 and 2008 from Caraş-Severin County indicated Giardia infections in 7.81% (21/269; 95% CI: 5.03–11.49) of individuals [90]. In addition, a study conducted by Costache et al between 2008 and 2011 in Cluj County and neighbouring areas reported a cumulative giardiasis prevalence of 0.41% (76/18,486; 95% CI: 0.33–0.51) in children and of 0.80% (141/17,645; 95% CI: 0.67–0.94) in the adult general population [91].…”
Section: Resultsmentioning
confidence: 99%
“…Other information regarding epidemiological and clinical characteristics of selected patient groups from different counties are provided in our retrospective studies (Neghina et al 2010c;Neghina et al 2011b;Neghina et al 2009a;Neghina et al 2009b;Neghina et al 2010h;Neghina et al 2010i;Neghina et al 2010j).…”
Section: Trichinellosismentioning
confidence: 99%